Pengaruh strategi metakognitif dalam pembelajaran berbasis masalah terhadap pencapaian hasil belajar fisika siswa kelas XI SMAN 4 Padang - anisa dwita fitri; amali putra (Universitas Negeri Padang, 2019)
One of the problems in physics learning in high school is that students are less able to solve various problems that are relevant to the subject matter, so student physics learning outcomes are still low. This research aims to determine the effect of the application of metacognitive strategy in problem-based learning to the results of physics learning of class XI students at SMAN 4 Padang in the first semester of the 2018/2019 academic year. This research is in the form of Quasi Experiment with the design of Posttest Only Control Gorup Design. The sampling technique was Cluster Random Sampling obtained by class XI MIPA 2 as the experimental class and class XI MIPA 1 as the control class. Research data was obtained through instruments in the form of LKS and tests in the form of learning outcomes data on aspects of knowledge. The instruments used have met the validity and reliability through trials. The results showed that the posttest results of the experimental class average value of 62.72 were higher than the average value of the control class of 55.34. The results of the t test at the 95% level indicate that tcount> t table, so that the difference in average values is due to differences in treatment. From the results of regression analysis and simple linear correlation between the value of using LKS and posttest in the experimental class, the value of rxy was 0.623, meaning that there were 38.81% contributions to the application of metacognitive strategy to student learning outcomes.